2009
DOI: 10.1017/s0008423909990424
|View full text |Cite
|
Sign up to set email alerts
|

Worth the Wait: Determinants of Ministerial Appointment in Canada, 1935–2008

Abstract: IntroductionThe exploration of ministerial careers has attracted considerable attention among political scientists in recent years~Dewan and Dowding, 2005;Dowding and Kang, 1998; Martinez-Gallardo, 2004, 2008;Kam, 2006;Kam and Indridason, 2005;Laver and Shepsle, 1994;Sutherland, 1991a; Woodhouse, 1993! The purpose of this article is to present a new perspective on a burgeoning area of study by focusing on ministerial appointments rather than the determinants of ministerial exit or survival. This article introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 26 publications
1
47
1
7
Order By: Relevance
“…Some authors have shown that women legislators have increased chances of being appointed minister (Cochrane : 73; Docherty ; Kerby ). Women's access to ministerial functions may be explained by the small pool of female legislators and the imperative of visibility; nowadays, it is more essential than ever to have women in cabinets (Docherty : 9, 59; White : 35–36).…”
Section: Review Of the Literature And Working Hypothesesmentioning
confidence: 99%
“…Some authors have shown that women legislators have increased chances of being appointed minister (Cochrane : 73; Docherty ; Kerby ). Women's access to ministerial functions may be explained by the small pool of female legislators and the imperative of visibility; nowadays, it is more essential than ever to have women in cabinets (Docherty : 9, 59; White : 35–36).…”
Section: Review Of the Literature And Working Hypothesesmentioning
confidence: 99%
“…[1] Indicative single country studies and comparative analyses are provided by Dumont, 2009, 2015;O'Malley, 2006;Kenig and Barnea, 2009;and Kerby, 2009.…”
Section: Notesmentioning
confidence: 99%
“…À titre d'exemple, une norme implicite veut que le premier ministre du Canada tienne compte de la représentation régionale et d'intérêts diversifiés au sein de son équipe de ministres (Kerby 2009;White 2005 : 40-42). Au Québec, Hamelin et Beaudoin (1967) précisent que, de 1867 à 1967, la composition des cabinets était sous l'influence du gouvernement fédéral, des impératifs géographiques, des groupes de pression et des qualités individuelles.…”
Section: La Sélection Des Membres De L'exécutifunclassified